BUILDING SPIRITUAL RESILIENCE IN THE ELDERLY THROUGH RELIGIOUS COUNSELING PROGRAMS: THE CASE OF MUHAMMADIYAH SENIOR CARE, PROBOLINGGO - Hidayah, Ulil (LPPM STAI Muhammadiyah Probolinggo, 2023)
Muhammadiyah Senior Care Probolinggo has held the community service program in order to fulfil this need by providing Islamic religious guidance as intervention for elderly residents in an effort to improve mental health, spiritual well-being, and social quality of life. Direct engagements served as the main method of penetration, allowing elderly to immerse themselves in the details and experience profound actions during three aspects (aqidah, ibadah, and akhlaq). The participants were comforted in aqidah now after being introduced to the compassionate attributes of Allah, i.e. merciful, and their fears of death started alleviating slowly as a result. Sessions of worship were held along with instructions on how to perform salah and opportunities for congregational prayer and dhikr (remembrance of Allah), forming a bond between the residents spiritually, as well as socially. Guidance of Ethics was to advance a harmonic interaction among care-centre, frequently conflicts were going on, so to merge people within peace and respect. Participatory Action Research (PAR) was applied in the study where the elderly residents actively participated as subjects of the guidance program. Three main phases — pre-guidance, guidance, and post-intervention — were followed in this methodology. The entire process consists of the initial stage by an observation and needs assessment by the guidance through previous meetings with the residence, then based on their history and condition material is designed that best suits them. This was held face to face both as a group and on individual basis in order for the material to be delivered at a pace that fits the capacity of participants. The group sessions were a good way to get people talking, and the individual sessions allowed for more depth and context. The last step was to evaluate the responses of participants and their progression to prepare a report that could be useful for similar programs. Its success is also due to the fact that it was not mandatory, and elderly were motivated to participate. Adaptive techniques like visual and audio methods or personal support helped facilitate understanding, although variability in educational backgrounds or physical limitations posed challenges. Tell the story of Prophets regularly, to draw inspiration from such events, which would assist the adults in absorbing faith-based principles practically. Such beneficial service helps the hawa nafsu of the elderly so that their spirit life can be well maintained in creating a harmonious atmosphere to prepare for the final phase of their life, with the hope of giving rise to Husnul Khotimah. Such a model may offer hope for other similar institutions in the years to come